Transformasi Pesantren Sebagai Fasilitator Ahli Hikmah (Studi Fenomenologi Pondok Pesantren Al-Insaf, Karangasem Utara, Batang) - Mochamad Aris Yusuf (Hikmah, 2023)
In the past, pesantren were the center for the ongoing transmission of traditional Islamic knowledge, as guardians and custodians of the continuity of traditional Islam, as well as centers for the reproduction of Islamic scholars. Now it has undergone a transformation in the form of solving socio-religious problems around it, such as the case of handling magic. So that the Al-Insaf Islamic Boarding School located in the Karang Widoro hamlet, North Karangasem, Batang, is here as a solution. This study uses a qualitative research method with a type of phenomenology. The purpose of this article is to reveal how the function of da'wah interaction is transformed at the al-Insaf Islamic boarding school, North Karangasem, Batang as a facilitator of wisdom. The results obtained in this study, experts of wisdom provide important information that magic can be cured as long as those affected by witchcraft try to recover, besides that interestingly, if the patient really wants to recover completely and can learn to fortify himself, he is given facilities, namely the Al-Insaf Islamic Boarding School. So, no one is afraid of disease, including magic. Meanwhile, persuasion lies in the appeal of the message brought by the wisdom expert.